Travailler avec François Gros à l’Institut Pasteur : l’allostérie, le récepteur nicotinique et la biologie du futur - Changeux, Jean-Pierre (Comptes Rendus Biologies, 2023)
Working with François Gros was a privileged moment in my scientific life, enabling me to appreciate a scientific personality whose generosity knew no bounds and whose vision of science was far ahead of its time.